Reflections about the Hippocratic Oath in Medical Education in Times of Artificial Intelligence (Revista Iberoamericana de Bioética, 2024)
In the 5th century BC, a medical school inspired by Hippocrates, a teacher of the art of healing, flourished in Greece. This school separated medicine from religion and magic and removed beliefs in supernatural causes of disease. Although scholars consider this more of a legend than a historical fact, 2,000 years later, Hippocrates is considered the “father of medicine” in the Western world.  Some of the 72 contemporary books from this school address medical ethics, including the Hippocratic Oath. With the development of humanity, social changes, and medical transformations, the oath underwent updates and has several versions. Some are used at special moments, such as in medical school graduations. Some unusual/ interesting/ reflecting situations regarding the oath motivated reflections on the use of it in medical teaching, including the emergence of Artificial Intelligence. Does the Oath still have a place in medical education?
Keywords: teaching; medical education; physician’s oath; artificial intelligence; medical professionalism; bioethics